Effect of low-dose dopamine on intestinal villus microcirculation during normotensive endotoxaemia in rats - Schmidt, Heinfried; Secchi, Andreas; Secchi, Ruth; Böhrer, Hubert; Bach, Alfons; Martin, Eike (British journal of anaesthesia, 1996)
Hypoperfusion of the gut mucosa is thought to be a factor in the development of gut barrier failure during sepsis and septic shock. Dopamine stimulates DA-1 receptors which mediate regional vasodilatation in the gut. Therefore, we have investigated the effect of low-dose dopamine (3 micrograms kg-1 min-1) on the intestinal villus microcirculation during endotoxaemia in a rat model of normotensive endotoxaemia, using in vivo videomicroscopy. Blood flow in and the diameters of central villus arterioles were measured before, immediately after and 60 min after a 1-h continuous infusion of endotoxin 1.5 mg/kg body weight. After baseline measurements were obtained, rats received either an infusion of 0.9% saline (group A; n = 7) or a volume-equivalent infusion of dopamine 3 micrograms kg-1 min-1 (group B; n = 7) throughout the study. Control animals (group C; n = 7) received no endotoxin or dopamine. In group A, villus blood flow (mean baseline 8.4 (SEM 0.9) nl min-1) decreased by 29.7 (8.9)% to 5.9 (0.9) nl min-1 immediately after endotoxin challenge and by a total of 43.1 (7.3)% to 4.7 (0.7) nl min-1 after another 60 min. Simultaneously, villus arteriolar diameters decreased from 7.8 (0.2) to 6.9 (0.3) microns and to 6.5 (0.3) microns, respectively. In group B, villus blood flow (baseline 8.7 (0.4) nl min-1) was unchanged immediately after the 1-h infusion of endotoxin (8.3 (0.4) nl min-1). However, another 60 min later blood flow decreased by 28.8 (8.0)% to 6.1 (0.7) nl min-1. In contrast with group A, the diameters of the central villus arterioles were unchanged despite administration of endotoxin (7.9 (0.2) microns; 8.1 (0.4) microns; 8.2 (0.5) microns). In group C, there were no changes in villus blood flow or arteriolar diameters throughout the study. Our results indicated that low-dose dopamine did not prevent, but delayed and attenuated, the decrease in intestinal villus blood during normotensive endotoxaemia.